Wind-driven circulation for the eastern North Atlantic Subtropical Gyre from Argo data - Fraile-Nuez, Eugenio; Hernández-Guerra, A. (Geophysical Research Letters, 2006)
A trans-oceanic section at 24.5°N in the North Atlantic has been sampled at a decadal frequency. This work demonstrates that the wind-driven component of the Meridional Overturning Circulation (MOC) may be monitored using autonomous profiling floats deployed in the eastern North Atlantic Subtropical Gyre. More than 500 CTD vertical profiles from the surface to 2000 m depth, spanning one year (from April 2002 to March 2003), are used to compute the geostrophic transport stream function at 24.5°N. The baroclinic transport obtained from the autonomous profiling floats is not statistically different than that from three hydrographic cruises carried out in 1957, 1981 and 1992. A good agreement is found between the geostrophic transport stream function and the transport derived from the wind field through the Sverdrup relation. No